Development of improved metaheuristic algorithms for modelling and control of a flexible manipulator system - Nasir, Ahmad Nor Kasruddin; Ahmad, Mohd Ashraf; Raja Ismail, R. M.T.; Muhammad Hamka, Embong (2019)
This project develops two variants of single-objective type optimization algorithm and two variants of multi-objective type optimization algorithm. The developed algorithms are formulated based on a spiral model approach and a sine model approach. The aim of the single type algorithms is to improve the algorithms capability to find an optimal solution. The algorithm is considered as more effective if the solution found has a higher accuracy. On the other hand, the aim for the multiobjective type algorithm is to find an optimal pareto front solution. A good pareto front should have a higher accuracy and a diverse solution along the pareto front. The performance of the developed algorithms are tested on various benchmark functions for both single and multiobjective type problems. It is found that all the developed algorithms have competitive accuracy performance compared to other state of the art algorithms i.e NSGA2, SCA, Sine-Cosine algorithms. In this work the algorithms are developed on a Matlab and Simulink software. The developed algorithms have been applied to optimize Proportional Integral Derivative (PID) controller parameters for a flexible manipulator system and an inverted pendulum system. The inverted pendulum system has almost the same control problem like the flexible manipulator system. It has a single input and multi output. In actual application, the output of interest are the position of a cart and angle of pendulum rod. Both angle and position must be controlled simultaneously to ensure the stability of the system during operation. The experiment has been performed on Matlab and Simulink software and verified on the actual inverted pendulum system. Actual application of these two system in industry include safe operation of an overhead crane to transfer object from one location to another location. Another application is the precise position control of surgery robot that widely used in hospital to help surgeon conduct various operations. The surgery robot has a flexible structure which is different to conventional industrial robot which has solid link. The project has been successfully implemented and a good result has been achieved. The research on controlling the crane and surgery robot should be carried on further. This is due to its advanced technology and complex system hence it requires lots of funds and a good research collaboration with industries is needed.